FILE DIN VIAŢA UNEI BISERICI ŞI A UNUI MITROPOLIT (III) - BOLDIŞOR, istoric, colaborator la Muzeul Literaturii Române „M. Kogălniceanu”, Veronica (BIBLIOPOLIS, 2020)
The author presents in this paper, one of the most difficult periods of the Metropolit Gurie Grosu activity: the 20s of the XX century, when was introduced the "New Style", alias the Gregorian calendar. As in Romania, in Bessarabia the opposition to this change was very strong from parishioners and clergy. Specific for Bessarabia is that there was strong the opposition fed from the outside, especially from the emissaries of the Russian Church in exile. In this complicated situation the metropolit G. Grosu showed calm, tact, patience, wisdom.